1984
DOI: 10.1073/pnas.81.22.7233
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the glucose transporter of the blood-brain barrier by cytochalasin B binding and immunological reactivity.

Abstract: ABSTRACT[3H]Cytochalasin B was used as a ligand to identify and characterize the glucose transporter in cerebral microvessels of the rat and the pig. Specific cytochalasin B binding, defined as that fraction of the total binding that is stereospecifically displaced by excess (500 mM) D-glucose, is saturable. Kinetic studies of this specific binding to cerebral microvessel preparations shQwed a dissociation constant (Kd) of 0.65-0.88 ,IM and a maximal binding (Bmax) of 60-80 pmol/mg of protein. In comparison, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
135
2
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(152 citation statements)
references
References 36 publications
14
135
2
1
Order By: Relevance
“…Our results indicate the presence of a single class of saturable binding sites with a similar dissociation constant for each subcellular fraction. The maximal binding capacity of the P 10000 x g fraction present in chromaffin tissue correlates well with similar fractions from cerebral cortex and cerebellum from pig and rat brain [10,11]. When more enriched fractions from neuroblastoma and astrocytes were compared, the values reported were also very similar to that found in chromaffin tissue membrane preparations (12-16 pmol/mg protein) [25].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results indicate the presence of a single class of saturable binding sites with a similar dissociation constant for each subcellular fraction. The maximal binding capacity of the P 10000 x g fraction present in chromaffin tissue correlates well with similar fractions from cerebral cortex and cerebellum from pig and rat brain [10,11]. When more enriched fractions from neuroblastoma and astrocytes were compared, the values reported were also very similar to that found in chromaffin tissue membrane preparations (12-16 pmol/mg protein) [25].…”
Section: Discussionsupporting
confidence: 72%
“…In all of the brain membranes the affinity constants are close to 0.3/zM [10]. Our results indicate the presence of a single class of saturable binding sites with a similar dissociation constant for each subcellular fraction.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Umezawa and Eto (1988) reported that liposomes bearing aminophenyl mannoside were efficiently taken up into the mouse brain, suggesting that mannose could be recognized by the cells of the BBB. The BBB cells are known to express high levels of the glucose transporter GLUT1 (Dick et al, 1984). Therefore, an active targeting based on GLUT1 ligands could be a useful strategy for drug delivery in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the large and uninterrupted energetic demand of the brain is provided almost exclusively by ␤-d-glucose. Furthermore, the glucose consumption of the brain amounts to about 30% of the total body glucose consumption (Dick et al, 1984;La Manna and Harik, 1985). This high level of cerebral glucose uptake suggests that the facilitative ␤-d-glucose transporter GLUT1 might be a useful carrier for efficient and selective glucose-targeted drug delivery to the brain.…”
Section: Introductionmentioning
confidence: 99%